‘You’re considered a warrior then’ - Marjo Väyrynen (Suomen Antropologi, 2011)
For many Crows, respect and the related value of individualism are central elements in their culture and social relations. They are commonly used to comprehend and conceptualize Crow military service as an institution, giving it distinctive cultural meaning and transforming it into a part of their own tradition. The notions of respect and individualism are also reflected in the admiration of tribal veterans that has priority over any elusive political concern with the veterans’ personal achievements and their role as embodiments of tribal values. In addition, they are repeatedly employed by the Crow in discussions of military service to construct their understanding of themselves as a respectful people, as opposed to Anglo-American society. Like many other indigenous peoples, the Crow today struggle to construct their lives on their own terms, and they do this by applying their traditional values, such as respect and individualism, to interpret reality and their own identity, hence perpetuating the essence of their distinctive way of life.